[PP.04.27] SERUM URIC ACID LEVEL COULD BE A PREDICTOR OF ATRIAL FIBRILLATION IN WOMEN BUT NOT IN MEN WITH METABOLIC SYNDROME. (September 2017) - Siliste, R.; Homentcovschi, C.; Vasiliu, D.; Savulescu-Fiedler, I.; Spataru, D.; Ianula, R.; Gurghean, A.
Abstract : Objective: Uric acid (UA) is a cardiovascular risk marker associated with oxidative stress and inflammation. Several studies showed the association of high levels of serum UA with atrial fibrillation (AF) in metabolic syndrome (MetS). The objective of this observational study was to investigate the gender differences of serum UA levels in patients with MetS and AF. Design and method: We evaluated 100 patients with MetS and AF (group A) and 50 patients with MetS without AF (group B), mean age 69, 28 ± 8, 8, respectively 59, 52 ± 9, 62 years, 68%F. We excluded subjects with coronary artery disease, congestive heart failure, valvular heart disease, congenital heart disease, cardiomyopathy, renal failure, inflammatory conditions, thyroid dysfunction, respiratory diseases, and those who were taking drugs that affect UA metabolism (apart from diuretics). Results: AF significantly correlated with older age (p < 0.001), decreased creatinine clearance (70, 39 ± 25, 89 vs. 88, 42 ± 23, 32 ml /min/1.73 m 2, p < 0.001), serum UA levels (6, 47 ± 1, 69 vs. 5, 49 ± 1, 80 mg / dl, p = 0.01), LA diameter (44, 3 ± 6, 33 vs. 39, 03 ± 5, 14 mm, p < 0.001) and LA volume (79, 31 ± 23, 68 vs. 57, 78 ± 15, 95 ml, p < 0.001). After multivariate logistic regression analysis, the independent predictors of AF were age and LA dimensions for both men and women. The serum UA was an independent predictor of AF only in women with MetS. The area under the receiver operating characteristic curve of serum UA for accuracy to detect atrial fibrillation in women was 0.87 (95% confidence interval 0.82–0.95). The cut-off point of 6.7 mg/dl had a sensitivity of 87% and a specificity of 79% to predict AF in women. Conclusions: Serum UA level was an independent predictor of AF in women but not in men with metabolic syndrome.